Utilization of Salak Sidimpuan (Salacca sumatrana Becc) as A Nata De Salacca Substrate in Sitaratoit Village South Tapanuli Selatan Sumatera Utara - Silitonga, Yusnita Wahyuni; Lubis, Rini Hayati; Harahap, Qorry Hilmiyah (Journal of Saintech Transfer, 2019)
Sitaratoit village is a village in South Tapanuli district, Nort Sumatera. The majority of people in that village drape his life from agriculture products. Major commodities agriculture product from the village is salak Sidimpuan. Knowledge about salak processing in village still very poor. Salak consumed or sold on condition fresh fruit. At some moment salak fruit can overproduction so the price is very low. A low price causing farmers did not harvest the salak which might cause waste. Nata de salacca product should be one of the alternative solutions to overcome this problem. The aims of the program were to provide information about salak waste treatment become nata de salacca. This program was initiated with the laboratory experiments and cooperate with local government and farmers. The following action was to acompany the farmers who aplicate the nata production process. Results from the laboratory experiment showed that the best composition of substrat and water ratiowas 1:4.